2021
DOI: 10.3390/antibiotics10010064
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Acquisition of Enterococcus faecium Infection and Mortality in Patients with Enterococcal Bacteremia: A 5-Year Retrospective Analysis in a Tertiary Care University Hospital

Abstract: The incidence of bacteremia caused by Enterococcus faecium, which is highly resistant to multiple antibiotics, is increasing in Japan. However, risk factors for the acquisition of E. faecium infection and mortality due to enterococcal bacteremia are not well known. We compared demographic, microbiological, and clinical characteristics using a Cox regression model and univariate analysis. We performed a multivariate analysis to identify risk factors for patients treated between 2014 and 2018. Among 186 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Chronic kidney disease has been described as a risk factor for enterococcal BSI in several studies, even if not focusing on BT-BSI ( 12 , 13 ). Finally, the use of carbapenems is a well-recognized risk factors for enterococcal bacteremia, and particularly for E. faecium ( 14 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease has been described as a risk factor for enterococcal BSI in several studies, even if not focusing on BT-BSI ( 12 , 13 ). Finally, the use of carbapenems is a well-recognized risk factors for enterococcal bacteremia, and particularly for E. faecium ( 14 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AST physicians follow the clinical course to determine whether a patient’s condition worsens after de-escalation. Although prior studies revealed that the administration of alternative broad-spectrum drugs is associated with worse clinical outcomes [ 18 , 19 ], we could avoid worse deterioration in patient outcomes even in an antimicrobial shortage period. Moreover, based on a multivariate analysis, Uda et al, reported that administration of broad-spectrum antibiotics, such as piperacillin/tazobactam, as definitive therapy was associated with treatment failure in patients with MSSA bacteremia during the CFZ shortage period (odds ratio = 17, p = 0.003) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study predicting the risk of VCM-induced acute kidney injury (AKI) reported that 32 (36.8%) of 87 patients who received vasopressors developed AKI and were being treated [14]. The development of AKI is thought to increase the risk of death from an enterococcal bloodstream invasion [15].…”
Section: Discussionmentioning
confidence: 99%